Evaluation of neutron induced reactions on 56Fe with CONRAD - Diakaki M.; Chen S.; Noguere G.; Bernard D.; Tamagno P.; Archier P. (EPJ Web of Conferences, 2020)
The evaluation of the 56Fe neutron induced reactions is currently ongoing at the CEA-Cadarache using the code CONRAD, with the goal to cover the whole energy range from the Resolved Resonance Region to the continuum and estimate the corresponding uncertainties and covariance matrices. Some first results and issues occurred from this work are presented and discussed here, more specifically on the analysed transmission and capture data in the Resolved Resonance Region, as well as the optical and statistical model calculations in the fast neutron energy range.